A Formula to Calculate the Threshold for Radiotherapy Targets on PET Images: Simulation Study - Geng, Jianhua; Luo, Fei; Tian, Jiahe; Zhang, Jinming; Zhang, Xiaojun; Qu, Baolin; Chen, Yingmao (Frontiers in Oncology, 2020)
Background: Positron emission tomography (PET) images are being applied for defining radiotherapy targets. However, a recognized method for defining radiotherapy targets is lacking. We investigate the threshold to outline the radiotherapy target of a tumor on PET images and its influencing factors, and then expressed it by formula. Methods: PET imaging for spherical tumors with a different tumor diameter (D), under different system resolutions (full width at half maximum (FWHM)), in different backgrounds with different pixel sizes, was simulated. PET images were analyzed to determine the relationship between the threshold and the factors mentioned above. Finally, the simulation results were verified by phantom experiments. Results: The threshold decreased sharply with D for D < 2 FWHM, reached the minimum of 31% at D = 2 FWHM and then increased slowly, and it tended to constant for D > 8 FWHM. The threshold decreased with FWHM for FWHM